Development of a novel strategy to reduce diagnostic errors in real-time polymerase chain reaction using probe-based techniques - Hyoung Jun Kim; Morten Schiøtt; Niels Jørgen Olesen; Euna Choi; Bok Kyung Ku; Kyoung Ki Lee; Hye Young Jeong; Ilseob Lee; Seong Mok Kim; Miyoung Cho; Young Chul Kim (Scientific Reports)
Abstract Real-time PCR assays are valuable tools for the rapid and accurate diagnosis of infectious diseases by identifying the nucleic acid sequences of pathogens. Here, we aimed to develop a recombinant plasmid-based standard for validating the sensitivity of different molecular diagnostic methods adopting the Jonstrup assay (J assay). Chimeric plasmid DNA (cpDNA) harboring various pathogen genes and the target site of the J assay was constructed. Our findings revealed that the J assay could detect a single copy of the target gene similar to digital droplet PCR. The detection sensitivity of each established real-time PCR method for various disease diagnoses was evaluated using the cpDNA. Although most methods showed high sensitivity, similar to that of the J assay, the VHS Garver and SARS-CoV-2 diagnostic methods exhibited detection sensitivities tenfold lower than that of the J assay. To ensure accuracy of results and avoid genetic contamination from positive controls, we introduced an additional probe attachment site emitting distinct fluorescent signals within the cpDNA. Target genes and exogenous sequences within the plasmid DNA were simultaneously detected in a single assay using this unique method. Our approach will help improve the sensitivity of diagnostic methods and develop novel diagnostic methods based on molecular techniques.